Comparative Evaluation of Six Different Storage Materials for Long-Term Preservation of Huckleberry (Solanum scabrum) Seeds - Mbeboh, Maurice Njiandoh; Youmbi, Emmanuel; Mala, William Armand; Manga, Gabriel Ambroise; Ngwa, Amos Funamo; Badjel, Sylvestre Medard Badjel; Ngosong, Christopher (International Journal of Sustainable Agricultural Research, 2019)
Smallholder farmers in Cameroon often store seeds from their own-harvest for use in subsequent planting seasons, but they have limited information on appropriate materials for long-term storage of vegetable seeds. Hence, six different materials (sealed aluminium foil sachet, sealed glass bottle, closed plastic cup, sealed paper sachet, sealed polythene sachet, and open-and-seal glass bottle) were evaluated for their effectiveness as storage materials for huckleberry seeds. Factorial ANOVA revealed significant (P < 0.001) effect of the different types of storage materials, duration of seed storage, and their interactions on laboratory germination, field emergence, and percentage transplantable see dlings. Significant (P < 0.05) variations were observed for laboratory seed germination and field emergence from months 2–5 of preservation across the different storage materials, with the highest performance exhibited by sealed aluminium foil sachet, while glass material exhibited the lowest performance. These performances decreased significantly (P < 0.05) for each storage material across months of long-term storage, with the lowest decrease recorded in sealed aluminium foil sachet and highest decrease recorded in glass bottle storage materials. Percentage transplantable seedlings decreased significantly (P < 0.05) from month 0–5 for each storage material, with lowest decrease in sealed aluminium foil sachet and highest decrease in open-and-seal glass bottle. Overall, these results demonstrate that sealed aluminium foil sachet is the most effective storage material for long-term preservation of huckleberry seeds under ambient conditions of the study area, which can be adopted by farmers.